PENGARUH DIMENSI KOMPETENSI TERHADAP KOMITMEN NORMATIF DIMODERASI KEPEMIMPINAN TRANSFORMASIONAL (STUDI KASUS DI PT. INDONESIA POWER UP. SEMARANG) - Restu Widya Rahayu, 13.05.51.0196 (Students' Journal of Economic and Management, 2017)
The purpose of this study is to determine the effect of competence on organizational commitment moderated transformational leadership in PT. Indonesia Power UP. Semarang. The population in this study are employees who work there as many as 350 people and a sample of 100 people. Hypothesis test in this research use regression analysis. Regression analysis results show that competence significantly influence organizational commitment moderated transformational leadership. The results of the analysis revealed that intellectual competence, emotional competence, social competence together affect the organizational commitment. Keywords: Competence, Organizational Commitment and Transformational Leadership